Ministry Of Finance Decree No. 185 Of The Year 2017 Concerning The Rules Governing The Payment Of The Monthly Special Raise Determined According To Law No. 77 Of The Year 2017 to State Servants Who Are Not Addressed By The Law On Civil Service Promulgated by Law no. 81 of the year 2016 = وزارة المالية قرار رقم 185 السنة 2017 بشأن قواعد صرف العلاوة الخاصة الشهرية المقررة بالقانون رقم 77 لسنة 2017 للعاملين بالدولة من غير المخاطبين بأحكام قانون الخدمة المدنية الصادر بالقانون رقم 81 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic